2016
DOI: 10.1177/1464420716637214
|View full text |Cite
|
Sign up to set email alerts
|

High cycle fatigue behavior of Al1070 alloy severely deformed by equal channel angular pressing process

Abstract: In the present work, equal channel angular pressing of commercial pure aluminum 1070 was performed up to 4 passes using route Bc. For equal channel angular pressing operation, a suitable die set was designed and manufactured. X-ray diffraction analysis was used to determine the microstructure of the equal channel angular pressing-ed material. The fracture surface morphology and microstructure after fatigue were investigated by scanning electron microscopy. Mechanical properties of the equal channel angular pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The increase of the Basqiun exponent after deformation processing, including SPD, has been frequently reported in the literature, e.g. [58][59][60], and this is associated with the strengthening effect, which tends to increase the susceptibility of the material to the internal imperfections inherited from SPD as well as to cyclically induced damage. Thus, compared to the as-cast state, the deformation processing increases the fatigue strength coefficient A in parallel with the microstructure refinement and the increasing monotonic strength.…”
Section: Fatigue Resistancementioning
confidence: 87%
“…The increase of the Basqiun exponent after deformation processing, including SPD, has been frequently reported in the literature, e.g. [58][59][60], and this is associated with the strengthening effect, which tends to increase the susceptibility of the material to the internal imperfections inherited from SPD as well as to cyclically induced damage. Thus, compared to the as-cast state, the deformation processing increases the fatigue strength coefficient A in parallel with the microstructure refinement and the increasing monotonic strength.…”
Section: Fatigue Resistancementioning
confidence: 87%
“…The base of the equal channel angular pressing (ECAP) is an extrusion process that is a severe plastic deformation technique. Recently, it has been demonstrated that ECAP can be used to produce bulk ultra-fine grained metals and alloys 10 that provides a potential for obtaining high strength 11 and enhanced superplasticity properties. 1215 With suitable mechanical properties and without discontinuity or porosity, ultra-fine grained materials obtained by ECAP have drawn significant interests from researchers during the recent two decades.…”
Section: Introductionmentioning
confidence: 99%